Quality, Value? – Insights into Medical Tourists' Attitudes and Behaviors. (July 2016) - Prajitmutita, Lyn Manassannan; Perényi, Áron; Prentice, Catherine
Abstract: The research investigates the factors influencing medical tourists' attitudes and behaviors. The factors examined include hospital service and customer perceived value. The study was undertaken in a major hospital located in a South-East Asian country. The sample includes foreign patients who have received various medical treatments in the hospital. The findings indicate that medical tourists are value oriented customers as their value perception has the strongest direct effect on their behaviors, followed by their attitudes towards the hospital. Hospital service appears to have a substantial direct effect on perceived value and medical tourist satisfaction, and also exerts an indirect effect on medical tourist behaviors. The research highlights the prominent role of perceived value, and pinpoints the most effective avenues for healthcare providers in allocating resources to improve hospital performance from the perspective of medical tourists.